The Stabilizing Effect of Li4Ti5O12 Coating on Li1.1Ni0.35Mn0.55O2 Cathode for Liquid and Solid–State Lithium-Metal Batteries - Hu, Wei; Zhong, Shengwen; Rao, Xianfa; Yan, Tingting; Zeng, Min (Frontiers in Energy Research, 2022)
Li–rich layered cathode materials with high energy density suffer from severe capacity decay during cycling, which is associated with volume change and electrolyte corrosion during (de)lithiation. A Li+ ionic conducting Li4Ti5O12 coating with high structural integrity is developed on Li1.1Ni0.35Mn0.55O2 cathodes via a dry powder coating method. The electrochemical performances of Li4Ti5O12–coated Li1.1Ni0.35Mn0.55O2 cathodes in liquid and solid–state lithium batteries were investigated. The initial discharge capacity of Li4Ti5O12–coated Li1.1Ni0.35Mn0.55O2 in the liquid electrolyte has been improved from 116.5 mA h g−1 to 123.7 mA h g−1 at 0.1°C. An impressive cyclability with a high capacity retention of 89.3% was achieved in solid–state lithium batteries. These results demonstrate that the Li4Ti5O12 coating plays an essential role in enhancing the specific capacity and better performance for Li1.1Ni0.35Mn0.55O2 cathode.